Effectiveness of exercise and physical activity interventions to improve long-term patient-relevant cognitive and non-cognitive outcomes in people living with mild cognitive impairment: a protocol of a systematic review and meta-analysis. Issue 8 (23rd August 2022) - Dieckelmann, Mirjam; Gonzalez-Gonzalez, Ana Isabel; Banzer, Winfried; Berghold, Andrea; Jeitler, Klaus; Pantel, Johannes; Schall, Arthur; Tesky, Valentina A; Siebenhofer, Andrea
Abstract : Introduction: Mild cognitive impairment (MCI) is a clinical syndrome characterised by persistent cognitive deficits that do not yet fulfil the criteria of dementia. Delaying the onset of dementia using secondary preventive measures such as physical activity and exercise can be a safe way of reducing the risk of further cognitive decline and maintaining independence and improving quality of life. The aim is to systematically review the literature to assess the effectiveness of physical activity and exercise interventions to improve long-term patient-relevant cognitive and non-cognitive outcomes in people living with MCI, including meta-analyses if applicable. Methods and analysis: We will systematically search five electronic databases from 1995 onward to identify trials reporting on the effectiveness of physical activity and exercise interventions to improve long-term (12+ months) patient-relevant cognitive and non-cognitive outcomes in adults (50+ years) with MCI. Screening procedures, selection of eligible full-texts, data extraction and risk of bias assessment will be performed in dual-review mode. Additionally, the reporting quality of the exercise interventions will be assessed using the Consensus on Exercise Reporting Template. A quantitative synthesis will only be conducted if studies are homogeneous enough for effect sizes to be pooled. Where quantitative analysis is not applicable, data will be represented in a tabular form and synthesised narratively. People living with MCI will be involved in defining outcome measures most relevant to them in order to assess in how far randomised controlled trials report endpoints that matter to those concerned. Ethics and dissemination: Results will be disseminated to both scientific and lay audiences by creating a patient-friendly video abstract. This work will inform professionals in primary care about the effectiveness of physical activity and exercise interventions and support them to make evidence-based exercise recommendations for the secondary prevention of dementia in people living with MCI. No ethical approval required. PROSPERO registration number: CRD42021287166.